Older cancer patients' information and support needs surrounding treatment: An evaluation through the eyes of patients, relatives and professionals - van Weert Julia CM; Posma Elise R; Jansen Jesse; Bensing Jozien M (BMC, 2009)
Abstract Background Providing cancer patients with adequate treatment information is important for patients' health, well-being and satisfaction. Nurses play an important role in patient education. So far, few studies focused on the specific information needs of older cancer patients surrounding chemotherapy treatment. Given the growing incidence of cancer among older individuals, insight in these needs is crucial. This article describes the views of older cancer patients, their relatives and professionals on older patients' specific communication needs regarding chemotherapy treatment. Methods A qualitative design was used. Five focus group interviews were held with older cancer patients and their partners (two groups) and professionals with a background in nursing, oncology, gerontology and/or patient-provider communication (three groups). In addition, face to face in-depth interviews were conducted with older cancer patients. A total number of 38 patients and relatives participated, with a mean age of 67.6 years. The focus groups and interviews were audio-recorded for subsequent transcription and analysis. Results Older people have more difficulties processing and remembering information than younger ones. A trustful environment appears to be a prerequisite for reflection of older patients on the information provided and individualized information is essential to enhance memory of information. However, the results show that both patients and professionals experienced insufficient exploration of the patients' personal situation and individual information needs. Patients also strengthened the importance of sensitive communication, e.g. showing empathy en emotional support, throughout the continuum of cancer care. Moreover, potential areas of improvement were identified, including engaging the patients' relatives and encouraging patients and relatives to ask questions. Conclusion Patient education should be more tailored to older cancer patients' individual information and support needs and abilities by exploring the required amount and content of information, treatment goals and expectations. Nurses can establish a trustful environment by showing empathy and emotional support. Recommendations are given to enhance recall of information in older patients; information giving should be more structured by summarizing and repeating the most important, personally relevant information. To adapt to specific information needs, communication training for nurses and the use of aids such as a question prompt sheet could be useful tools.